Magnetic resonance index of activity (MaRIA) and Clermont score are highly and equally effective MRI indices in detecting mucosal healing in Crohn's disease. Issue 11 (November 2017) - Buisson, Anthony; Pereira, Bruno; Goutte, Marion; Reymond, Maud; Allimant, Christophe; Obritin-Guilhen, Hélène; Bommelaer, Gilles; Hordonneau, Constance
Abstract: Background: Magnetic resonance index of activity (MaRIA) and Clermont score are currently the two main MRI indices that have been validated compared to endoscopy in Crohn's disease (CD). Aims: To compare the accuracy of MaRIA and Clermont score in assessing CD mucosal healing. Methods: Fourty-four CD patients underwent prospectively and consecutively MRI and colonoscopy. Results: Considering 207 segments, MaRIA > 7 and Clermont score > 8.4 demonstrated substantial accuracy to detect endoscopic ulcerations (73.9% and 74.0%, respectively) and presented with high specificity (82.1% and 81.3%) and high negative predictive value (NPV) (82.1% and 82.4%) for MaRIA and Clermont score, respectively. The sensitivity for detecting deep ulcerations was 90.9% for both MaRIA > 11 and Clermont score > 12.5, with a specificity of 82.0% and 80.0%, respectively. Among 44 patients, deep MRI remission predicted mucosal healing with specificity = 85.3% and NPV = 85.3% according to Barcelona criteria (no segmental MaRIA > 7), and specificity = 88.2% and NPV = 85.7% according to Clermont criteria (no segmental Clermont score > 8.4). In addition, MRI remission predicted mucosal healing with specificity = 76.5% and NPV = 86.7% according to Barcelona criteria (no segmental MaRIA > 11), and specificity = 79.4% and NPV = 84.4% according to Clermont criteria (no segmental Clermont score > 12.5). Conclusion: MaRIA and Clermont score are equally effective in detecting CD endoscopic ulcerations supporting their use as therapeutic endpoints.